Hard to Get : Twenty-Something Women and the Paradox of Sexual Freedom (Book collections on Project MUSE., 2013)
"Hard to Get is a powerful and intimate examination of the sex and love lives of the most liberated women in history-twenty-something American women who have had more opportunities, more positive role models, and more information than any previous generation. Drawing from her years of experience as a researcher and a psychotherapist, Leslie C. Bell takes us directly into the lives of young women who struggle to negotiate the complexities of sexual desire and pleasure, and to make sense of their historically unique but contradictory constellation of opportunities and challenges. In candid interviews, Bell's subjects reveal that, despite having more choices than ever, they face great uncertainty about desire, sexuality, and relationships. Ground-breaking and highly readable, Hard to Get offers fascinating insights into the many ways that sex, love, and satisfying relationships prove surprisingly elusive to these young women as they navigate the new emotional landscape of the 21st century."--